A study of the General English curriculum to find out how far it caters to the job opportunities in the private sector. - Lakshmi, G.S.V. (My University, 2006)
The liberation of economic policies, as well as factors such as globalization have made the Private sector of Sri Lanka, its engine of growth. Consequently the private sector figures as a major provider of employment opportunities. One of the aspects that the private sector looks in its new recruits is the competency in the English Language. In order to provide this competency, General English was introduced in the Advanced Level curriculum. Despite this, lack of competency in the English language among Sri Lankan government school leavers have made them virtually unemployable in the private sector. The research questions guiding this study are to determine whether the curriculum of the Advanced level General English meets the demand of the private sector and if the Advanced level students are confident in gaining employment in the private sector. This survey consists of a randomized sample of two hundred and fifty students who have completed the Advanced Level Examination with English as a subject and following the Practical English course at Royal Institute and four human resource managers of four leading private companies. Methodology of the study has been the administration of a structured questionnaire for the Personnel Managers. Among the Practical English students a random sample of two hundred were selected to administer the questionnaire and the balance fifty students were interviewed to triangulate the data obtained through the questionnaire. The data was analysed using descriptive and statistical methods. The findings of the study suggest that the curriculum does not totally cater to the needs of the private sector and further more external factors too have hindered the program in achieving its objectives. It is recommended that to make the advanced level school leavers more employable, the curriculum should emphasise more in developing the speaking and listening skills. These skills should be based on Task Based Learning and Problem Based Learning